Nectar Production in Oilseeds: Food for Pollinators in an Agricultural Landscape. Issue 2 (1st March 2016) - Thom, Matthew D.; Eberle, Carrie A.; Forcella, Frank; Gesch, Russ; Weyers, Sharon; Lundgren, Jonathan G.
Abstract : Pollinating insects are in decline throughout the world, driven by a combination of factors including the loss of forage resources. The maize ( Zea mays L.)– and soybean [ Glycine max (L.) Merr.]–dominated agriculture of the Central and Midwestern United States produces a landscape relatively devoid of nectar and pollen resources. Introducing specialty oilseeds into current crop rotations could provide abundant floral resources for pollinating insects as well as a high‐value crop for growers. We investigated the nectar sugar resources and insect visitation throughout flower anthesis of nine specialty oilseed crops in west‐central Minnesota and eastern South Dakota during the 2013 and 2014 growing seasons. Total sugar produced over anthesis (TS) was highest for echium ( Echium plantagineum L.) at 472 kg ha −1 . Canola ( Brassica napus L.), crambe ( Crambe abyssinica Hochst.), echium, borage ( Borago officinalis L.), and cuphea ( Cuphea viscosissima Jacq. × Cuphea lanceolata W. T. Aiton) produced enough sugar in one hectare to supply the annual sugar needs of a least one managed honey bee ( Apis mellifera L.) colony. Pollinators visited flowers of all crops, with as many as 90 insects min −1 observed. Our study is unique as we measured nectar sugar production, flower density, and insect visitation throughout anthesis for multiple specialty oilseed crops, providing a seasonwide perspective of the flux of nectar resources for pollinators. Adding specialty oilseed crops into current crop rotations could aid in reversing pollinator decline by providing forage resources that are lacking in the current agricultural landscape.